2022
DOI: 10.2147/phmt.s361188
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Abnormalities in Culture Positive Neonatal Sepsis

Abstract: Background In neonatal sepsis, anemia, leukocytosis, thrombocytopenia, and a shortened coagulation time are the most common hematologic abnormalities. However, there is inadequate information regarding the hematological abnormalities in neonatal sepsis. Thus, we aimed to determine the magnitude of hematological abnormalities in neonatal sepsis. Methods This is a cross-sectional study that included 143 neonates with culture proven sepsis aged 1–28 days from September 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In terms of hematological changes, leucopenia (WBCs of <3,000/mm 3 ) was evident in 7.8% of infected neonates. This finding is similar to results reported by Adane et al 25 and Diakité et al 26 …”
Section: Discussionsupporting
confidence: 93%
“…In terms of hematological changes, leucopenia (WBCs of <3,000/mm 3 ) was evident in 7.8% of infected neonates. This finding is similar to results reported by Adane et al 25 and Diakité et al 26 …”
Section: Discussionsupporting
confidence: 93%
“…PLT levels decreased by 17.0% in neonates with gram-positive septicaemia. 19 In addition, the results of this study show that there was no difference in MPV levels between the two groups in the early stage of infection; MPV levels increased in both groups during the recovery stage (compared with the early stage) and MPV/PLT ratios increased in the early stage. However, since MPV in the early stages of infection did not differ, multivariate logistic regression analysis showed that the MVP/PLT ratio is not an early predictor of severe neonatal infection; this result is inconsistent with the findings of related studies.…”
Section: Discussionmentioning
confidence: 56%
“… 18 The results of this study show that the probability of a decreased WBC level in severe neonatal infection is higher than the probability of an increased WBC level, which is consistent with the results of studies from other countries. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, anemia is a prevalent characteristic observed in the adult population during sepsis, resulting from iatrogenic blood loss, reduction in serum iron levels and erythropoietin synthesis, and a decrease in the lifespan of erythrocytes [35]. Regarding the neonatal population, a study by Adane et al showed that the prevalence of anemia in neonates with sepsis is 49% [36].…”
Section: Discussionmentioning
confidence: 99%